(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Contributo sottoposto a valutazione SOMMARIO: 1. Il problema del simbolismo religioso sul luogo di lavoro – 2. La soluzione per la Giurisprudenza francese – 3. La soluzione per la Corte EDU – 4. Considerazioni conclusive. ABSTRACT The author of this paper comments some recent judgments of the FrenchCour de Cassation and of the European Court of Human Rights concerns the exercise of religious freedom in the workplace. The examination shows somecritic aspects of this right in Europe.